2012
DOI: 10.2139/ssrn.2102420
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Markets for Economic Forecasting

Abstract: Prediction markets-markets used to forecast future events-have been used to accurately forecast the outcome of political contests, sporting events, and, occasionally, economic outcomes. This chapter summarizes the latest research on prediction markets in order to further their utilization by economic forecasters. We show that prediction markets have a number of attractive features: they quickly incorporate new information, are largely efficient, and impervious to manipulation. Moreover, markets generally exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The potential of these markets to forecast event outcomes has generated significant interest among social scientists and the business community, while corporations use prediction markets as a decision support tool (O'Leary, D.E., 2015, Spears et al, 2009. Prediction markets also have many potentially valuable applications for public policy (Paton et al, 2010;Tetlock et al, 2017) and for economic forecasting (Snowberg et al, 2013). A separate focus of attention has been the design of the market mechanisms used in prediction markets (Chen, 2011;Klingert and Meyer, 2018;Spann and Skiera, 2003).…”
mentioning
confidence: 99%
“…The potential of these markets to forecast event outcomes has generated significant interest among social scientists and the business community, while corporations use prediction markets as a decision support tool (O'Leary, D.E., 2015, Spears et al, 2009. Prediction markets also have many potentially valuable applications for public policy (Paton et al, 2010;Tetlock et al, 2017) and for economic forecasting (Snowberg et al, 2013). A separate focus of attention has been the design of the market mechanisms used in prediction markets (Chen, 2011;Klingert and Meyer, 2018;Spann and Skiera, 2003).…”
mentioning
confidence: 99%
“…focusing on economic indicators(Snowberg et al 2012) found a survey of business expectations did not encompass either initial unemployment claims or retail sales, suggesting the business confidence, and the labour force and retail series were complementary, and did not overlap in terms of the economic information provided. In essence, each series had informational value for market participants.Another important issue in comparing the relative performance of prediction markets and polls in forecasting elections concerns the temporal horizons.…”
mentioning
confidence: 99%